Perceptions of physical activity in adolescents with low physical activity levels - Ugu, Sisilia Anggelia; Arianti, Rudangta (Universitas Negeri Malang, 2023)
Insufficient engagement in physical activity is one of the most common and persistent contributors to poor health worldwide. This research was conducted to investigate physical activity perceptions in adolescents with low physical activity. This research predominantly qualitative methodologies to elaborate on perceptions of physical activity, individual preferences, and factors that hinder the experiences of adolescents with low physical activity levels. The International Physical Activity Questionnaire-Short Form (IPAQ-SF) was administered randomly to adolescents aged 18-21 to identify adolescents with low physical activity levels who had less than 1 hour per day or did not meet moderate to vigorous physical activity levels. Semi-structured interviews were conducted with adolescents with low physical activity levels based on IPAQ norm calculations. Interviews were analyzed using thematic analysis. The main themes identified, namely misperceptions about physical activity, perceived ambiguity of social support, and perception of risk to understand the perception of physical activity in adolescents with low physical activity levels.